Work - Pietrykowski, Bruce (Cambridge, U.K. : Polity Press, 2019)
"Much of our life involves working, preparing for work, searching for work, or thinking and worrying about work. Whether paid or unpaid, free or coerced, full time, part time or zero hours, work defines us and helps shape our behavior both on and off the job. In this accessible book, leading labor economist Bruce Pietrykowski offers a highly engaging exploration of the history and contemporary organization of work under capitalism. His clear presentation of the theoretical debates is illustrated by real-world examples from across the globe and a skilful account of alternatives that point toward a post-capitalist future. Employing a progressive, worker-centered vision that goes beyond neoclassical economics, he examines themes ranging from inequality, care work, and the gig economy to technological change and universal basic income. His analysis emphasizes power, conflict, solidarity, and cooperation, interpreted through the lens of class, race, gender and place. This comprehensive and highly readable book will be of interest to students of economics, sociology, labor studies and politics seeking to learn more about work and workers in the global economy, as well as interested general readers"--
"In this accessible book, leading labor economist Bruce Pietrykowski offers a highly engaging exploration of the history and contemporary organization of work under capitalism. Employing a progressive, worker-centered vision that goes beyond neoclassical economics, he examines a wide range of themes that characterize twenty-first century work"--
Introduction: The Unique Character of Work -- Inequality at Work: Skills, Wages and Productivity -- Gender at Work: Caring Labor -- Managerial Strategies: Low Road vs. High Road and Off-Road -- Beyond Managerial Strategies: Worker Cooperatives -- Technology, Automation and Skills: Restructuring the Workplace -- Conclusion: Future Worlds of Work -- Notes -- Reference -- Index.
Includes bibliographical references (pages 133-150) and index.
Keywords: Work; Equality; Income distribution; Economic policy